(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Human Immunodeficiency virus (HIV) infection is associated with increased of developing heart disease. Information on the cardiac status of HIV-infected Nigerians is lacking. HIV/AIDS infection is a global pandemic and poses a serious health challenge in sub-Saharan Africa, Nigeria inclusive. The cardiac disease may occur at any stage of HIV infection, but important manifestations are more frequent with advanced immunodeficiency. Moreover, it has been reported that complications from HIV infection include arrhythmias, heart failure myocardial infarction and coronary heart disease. This study aimed to estimate serum levels of AST, LDH, CKMB and TCK among HIV patients on HAART, HAART naïve and controls subjects attending Bauchi State Tertiary hospital, Nigeria. The results showed that the mean serum total Creatine kinase, CK-MB, LDH and AST were significantly higher in HIV participants not on HAART compared with HIV participants on HAART at P<0.05 respectively. Similarly, the mean serum total Creatine kinase, CK-MB, LDH and AST were significantly higher in symptomatic HIV participants not on HAART compared with HIV seronegative control subjects at P<0.05 in each case. Once again, the mean serum total Creatine kinase, CK-MB, LDH and AST were significantly higher in asymptomatic HIV participants compared with HIV seronegative control subjects at P<0.05 respectively. Increased levels of some cardiac markers were seen in HIV-infected participants. The study reveals that there is a need to monitor these parameters to prevent sudden cardiovascular complications in HIV seropositive patients. Hence, it is recommended that more investigations need to be carried out to further evaluate the levels of CK-MB (cardiac-specific) isoenzyme of CK and other cardiac biomarkers such as troponins I and T, and myoglobin, among others.